Monitoring process of developing system for providing temperature, air supply and filtration of transported control modules - A. A. Girchenko; A. A. Rumyantsev; A. A. Kazantsev; D. I. Bukhanets; A. V. Timoshenko; A. A. Murashev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article presents an approach to formalizing the process of creating a system for providing temperature, air supply and filtration (TAFS) of transported control modules of aerospace defense complexes. The use of line graphs to control the creation of such systems has recently shown its inconsistency and requires improvement in terms of how to manage the processes of creating such systems. As a basis, it is proposed to use the dynamic theory of graphs, which allows one to take into account not only resource-time constraints, but also possible changes in the structure of relations of sequences of work performed to create TAFS. The paper shows that the key element of managing the process of creating TAFS is a complex modeling stand, which can be used to obtain objective data on the development of system equipment. The availability of this information allows taking control on the process of creating TAFS at all stages of the life cycle using a network model. The composition and structural diagram of such a stand are given in the article